Habitat and Host Species Drive the Structure of Bacterial Communities of Two Neotropical Trap-Jaw Odontomachus Ants: Habitat and Host Species Drive the Structure of Bacterial Communities of Two Neotropical Trap-Jaw Odontomachus Ants - Rocha, Felipe P.; Ronque, Mariane U. V.; Lyra, Mariana L. [UNESP]; Bacci, Maurício [UNESP]; Oliveira, Paulo S. (Springer Nature, 2022)
Antshave long been known for their associations with other taxa, including macroscopic fungi and symbiotic bacteria. Recently, many ant species have had the composition and function of their bacterial communities investigated. Due to its behavioral and ecological diversity, the subfamily Ponerinae deserves more attention regarding its associated microbiota. Here, we used the V4 region of the 16S rRNA gene to characterize the bacterial communities of Odontomachus chelifer (ground-nesting) and Odontomachus hastatus (arboreal), two ponerine trap-jaw species commonly found in the Brazilian savanna (“Cerrado”) and Atlantic rainforest. We investigated habitat effects (O. chelifer in the Cerrado and the Atlantic rainforest) and species-specific effects (both species in the Atlantic rainforest) on the bacterial communities’ structure (composition and abundance) in two different body parts: cuticle and gaster. Bacterial communities differed in all populations studied. Cuticular communities were more diverse, while gaster communities presented variants common to other ants, including Wolbachia and Candidatus Tokpelaia hoelldoblerii. Odontomachus chelifer populations presented different communities in both body parts, highlighting the influence of habitat type. In the Atlantic rainforest, the outcome depended on the body part targeted. Cuticular communities were similar between species, reinforcing the habitat effect on bacterial communities, which are mainly composed of environmentally acquired taxa. Gaster communities, however, differed between the two Odontomachus species, suggesting species-specific effects and selective filters. Unclassified Firmicutes and uncultured Rhizobiales variants are the main components accounting for the observed differences. Our study indicates that both host species and habitat act synergistically, but to different degrees, to shape the bacterial communities in these Odontomachus species.
Keywords: 16S rRNA gene; Atlantic Rainforest; Bacterial communities; Cerrado; Odontomachus; Ponerinae